Systematic review and meta‐analysis of the prevalence of smokeless tobacco consumption among adults in Bangladesh, India and Myanmar. Issue 7 (21st May 2020) - Naznin, Eva; Wynne, Olivia; George, Johnson; Hoque, Mohammad Enamul; Milton, Abul Hasnat; Bonevski, Billie
Abstract: Objective: To estimate the pooled prevalence of smokeless tobacco consumption (STC) by gender and location in Bangladesh, India and Myanmar and to identify periodic changes in STC prevalence using data extracted from published studies. Methods: We searched for a combination of keywords in electronic databases and used a standard form to extract data from each article. We undertook a meta‐analysis to estimate pooled prevalence and confidence intervals within these countries. To compare periodic changes in STC prevalence, we grouped studies into five‐year periods (2000–2004, 2005–2009, 2010–2014 and 2015–2019). Results: The pooled estimates of STC prevalence were 25% (95% CI: 22–28%), 22% (95% CI: 15–28%) and 21% (95% CI: 14–28%) for Bangladesh, India and Myanmar, respectively. In pooled estimates across these countries, we found higher STC prevalence for men (30%; 95% CI: 24–35%) than women (16%; 95% CI: 10–23%) and for rural dwellings (24%; 95% CI: 18–31%) than urban dwellings (17%; 95% CI: 10–24%). We found significant decrease in STC in Bangladesh and India in the period 2010–2014 and 2015–2019, respectively. In Myanmar, STC prevalence increased significantly and substantially in 2010–2014, to levels higher than in Bangladesh and India. Conclusions: The prevalence of STC in Bangladesh, India and Myanmar is highest in rural areas and among men. Public health prevention strategies are needed to maintain decrease in STC in Bangladesh and India, and to reverse the increased use in Myanmar. Abstract : Objectif: Estimer la prévalence poolée de la consommation de tabac sans fumée (CTSF) par sexe et lieu au Bangladesh, en Inde et au Myanmar et identifier les changements périodiques de la prévalence des CTSF à l'aide de données extraites d'études publiées. Méthodes: Nous avons recherché une combinaison de mots‐clés dans les bases de données électroniques et utilisé un formulaire standard pour extraire les données de chaque article. Nous avons entrepris une méta‐analyse pour estimer la prévalence poolée et les intervalles de confiance dans ces pays. Pour comparer les changements périodiques de la prévalence des CTSF, nous avons regroupé les études en périodes de cinq ans (2000‐2004, 2005‐2009, 2010‐2014, 2015‐2019). Résultats: Les estimations poolées de la prévalence des CTSF étaient de 25% (IC95%: 22‐28%), 22% (IC95%: 15‐28%) et 21% (IC95%: 14‐28%) pour le Bangladesh, l'Inde et le Myanmar, respectivement. Dans les estimations poolées de ces pays, nous avons constaté une prévalence des CTSF plus élevée pour les hommes (30%; IC95%: 24‐35%) que pour les femmes (16%; IC95%: 10‐23%) et pour les habitations rurales (24%; IC95%: 18‐31%) que les habitations urbaines (17%; IC95%: 10‐24%). Nous avons constaté une diminution significative des CTSF au Bangladesh et en Inde au cours de la période 2010‐2014 et 2015‐2019 respectivement. Au Myanmar, la prévalence des CTSF a augmenté de manière significative et substantielle en 2010‐2014, à des niveaux plus élevés qu'au Bangladesh et en Inde. Conclusions: La prévalence des CTSF au Bangladesh, en Inde et au Myanmar est la plus élevée dans les zones rurales et chez les hommes. Des stratégies de prévention de la santé publique sont nécessaires pour maintenir la diminution des CTSF au Bangladesh et en Inde et pour inverser l'augmentation de la consommation au Myanmar.